2021
DOI: 10.1186/s12903-021-01885-6
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effect of ligature-induced periodontitis on cardiovascular variability and inflammatory response in spontaneously hypertensive rats

Abstract: Background We previously reported that periodontal disease (PD) induces high arterial pressure variability (APV) consistent with sympathetic overactivity and elicits myocardial inflammation in Balb/c mice. However, it is unknown whether PD can change APV and heart rate variability (HRV) in spontaneously hypertensive (SHR) and normotensive Wistar-Kyoto (WKY) rats. This study aimed to evaluate the hemodynamic level, HRV, and APV associating with myocardial inflammation and plasma concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Similar to investigations that analyzed changes in autonomic nervous system activity using frequency‐domain analysis, other studies have used time‐domain analysis of HRV. As in frequency‐domain studies, baseline values not only in sham groups were used (Abulaiti et al, 2011; De La Fuente et al, 2013; Houshmand et al, 2017; Krüger et al, 1997, 2000; Lima et al, 2018; Müller‐Ribeiro et al, 2017; Sallam et al, 2016, 2017; Silva, Geraldini, et al, 2017; Silva, Silva, et al, 2017; Soler et al, 2018; Wang et al, 2016; Xu et al, 2020), but also from groups in which the values were recorded only before the experimental intervention itself and the animals did not undergo surgical preparation (control) (Barbier et al, 2006; Beckers et al, 2006; Beltrán et al, 2020; Couderc et al, 2002; Farraj et al, 2009; Fazan Jr. et al, 2015; Hashimoto et al, 1999; Hazari et al, 2021; Koresh et al, 2016; Lamb et al, 2012; Lin et al, 2016; Maida et al, 2017; Mangin et al, 1998; Mostarda et al, 2009; Pereira‐Junior et al, 2010; Powell et al, 2021; Ramaekers et al, 2002; Ribeiro et al, 2021; Saalfield & Spear, 2014; Scridon et al, 2012; Shi et al, 2017; Simoes et al, 2016; Zajączkowski et al, 2018).…”
Section: Hrv: Control (Baseline) Values From Frequency‐domain Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to investigations that analyzed changes in autonomic nervous system activity using frequency‐domain analysis, other studies have used time‐domain analysis of HRV. As in frequency‐domain studies, baseline values not only in sham groups were used (Abulaiti et al, 2011; De La Fuente et al, 2013; Houshmand et al, 2017; Krüger et al, 1997, 2000; Lima et al, 2018; Müller‐Ribeiro et al, 2017; Sallam et al, 2016, 2017; Silva, Geraldini, et al, 2017; Silva, Silva, et al, 2017; Soler et al, 2018; Wang et al, 2016; Xu et al, 2020), but also from groups in which the values were recorded only before the experimental intervention itself and the animals did not undergo surgical preparation (control) (Barbier et al, 2006; Beckers et al, 2006; Beltrán et al, 2020; Couderc et al, 2002; Farraj et al, 2009; Fazan Jr. et al, 2015; Hashimoto et al, 1999; Hazari et al, 2021; Koresh et al, 2016; Lamb et al, 2012; Lin et al, 2016; Maida et al, 2017; Mangin et al, 1998; Mostarda et al, 2009; Pereira‐Junior et al, 2010; Powell et al, 2021; Ramaekers et al, 2002; Ribeiro et al, 2021; Saalfield & Spear, 2014; Scridon et al, 2012; Shi et al, 2017; Simoes et al, 2016; Zajączkowski et al, 2018).…”
Section: Hrv: Control (Baseline) Values From Frequency‐domain Analysismentioning
confidence: 99%
“…In in vivo experiments involving awake or freely moving animals, baseline values are used from sham groups, when the animals, in addition to the implantation of electrodes for continuous ECG recording, are also subjected to other surgical procedures as preparation for the further course of the experiment, but without subsequent targeted experimental intervention. For example, preparation for coronary or femoral artery occlusion (Aires et al, 2017; De La Fuente et al, 2013; Nobre et al, 2006), catheterization (Beckers et al, 2006; Blanco et al, 2015; Fiorino et al, 2012; Krüger et al, 1997, 2000; Mostarda et al, 2009; Müller‐Ribeiro et al, 2017; Quagliotto et al, 2015; Ramaekers et al, 2002; Ribeiro et al, 2021; Sallam et al, 2016, 2017; Shi et al, 2020; Simoes et al, 2016), ligation (Lima et al, 2018; Maida et al, 2017; Ruiz et al, 2014; Wang et al, 2016), bile duct ligation (Haddadian et al, 2013), cannulation (Beltrán et al, 2020; Da Silva et al, 2002; Neto et al, 2017; Sant'Ana et al, 2011), implantation of stimulators (Dai et al, 2020; Domingos‐Souza et al, 2021), or if they have already been administered substances beforehand (Lo Giudice et al, 2002).…”
Section: Hrv: Control (Baseline) Values From Frequency‐domain Analysismentioning
confidence: 99%
“…In Balb/c mice our group demonstrated that the experimental model of periodontitis impacts the overall arterial pressure variability and cardiac performance, increasing sympathetic modulation of cardiac function and myocardial inflammation [71]. In spontaneously hypertensive rats (SHR), we observed that short-term periodontitis lowered the arterial pressure, probably due to the higher levels of plasma nitric oxide levels [72]. Even though periodontitis did not affect either heart rate variability or arterial pressure variability, but induced myocardial inflammation, it could determine long-term cardiovascular dysfunction [72].…”
Section: Studies In Conscious Animals Involving the Autonomic Nervous...mentioning
confidence: 99%
“…In spontaneously hypertensive rats (SHR), we observed that short-term periodontitis lowered the arterial pressure, probably due to the higher levels of plasma nitric oxide levels [72]. Even though periodontitis did not affect either heart rate variability or arterial pressure variability, but induced myocardial inflammation, it could determine long-term cardiovascular dysfunction [72]. Thus, we investigated whether the baroreceptor and chemoreceptor reflexes would control the inflammatory process associated with periodontitis [73].…”
Section: Studies In Conscious Animals Involving the Autonomic Nervous...mentioning
confidence: 99%